Exercise Related Respiratory Problems in the Young—Is It Exercise-Induced Bronchoconstriction or Laryngeal Obstruction? - Vollsæter, Maria; Stensrud, Trine; Maat, Robert; Halvorsen, Thomas; Røksund, Ola Drange; Sandnes, Astrid; Clemm, Hege (Frontiers in Pediatrics, 2022)
Complaints of breathlessness during heavy exercise is common in children and adolescents, and represent expressions of a subjective feeling that may be difficult to verify and to link with specific diagnoses through objective tests. Exercise-induced asthma and exercise-induced laryngeal obstruction are two common medical causes of breathing difficulities in children and adolescents that can be challenging to distinguish between, based only on the complaints presented by patients. However, by applying a systematic clinical approach that includes rational use of tests, both conditions can usually be diagnosed reliably. In this invited mini-review, we suggest an approach we find feasible in our everyday clinical work.